1995
DOI: 10.1159/000129415
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Liver Injury after Partial Hepatectomy with Intermittent or Continuous Hepatic Vascular Occlusion

Abstract: The degree of residual liver injury in normal and cirrhotic rats undergoing 70% hepatectomy with hepatic inflow occlusion was examined. The total duration of clamping was 60 min and animals were divided into 3 groups according to the ischemic modality: a 15-min intermittent clamping group (group I); a 30-min intermittent clamping group (group II), and a 60-min continuous clamping group (group III). In normal liver rats, the survival rates after operation in groups I, II and III were 90, 90 and 30%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 11 publications
1
31
0
4
Order By: Relevance
“…Liver resections are frequently performed under complete or partial vascular occlusion to reduce blood loss, and it has been shown that intermittent rather than continuous pedicle occlusion leads to lower postoperative morbidity and mortality rates. 2,4,[20][21][22][23] Significant improvement of postoperative liver function has been observed in rats 22 and humans after intermittent ischemia. 23 Recently, Sakamoto et al 24 showed that the upper limit of cumulative intermittent hepatic ischemia could be extended to 322 minutes without any postsurgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Liver resections are frequently performed under complete or partial vascular occlusion to reduce blood loss, and it has been shown that intermittent rather than continuous pedicle occlusion leads to lower postoperative morbidity and mortality rates. 2,4,[20][21][22][23] Significant improvement of postoperative liver function has been observed in rats 22 and humans after intermittent ischemia. 23 Recently, Sakamoto et al 24 showed that the upper limit of cumulative intermittent hepatic ischemia could be extended to 322 minutes without any postsurgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Com o objetivo de minimizar as lesões provocadas pela isquemia e pela reperfusão alguns estudos foram elaborados utilizando a manobra de Pringle por curtos perío-dos, seguidos de reperfusão em vários ciclos [7][8][9][10][11][12][13][14] . Teoricamente, nos pequenos intervalos em que o órgão era perfundido haveria retorno da atividade aeróbia, o que diminuiria a produção de ácido láctico e radicais livres, já sabidamente envolvidos na etiologia da lesão celular.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Entretanto, vários trabalhos que compararam os dois tipos de clampeamento, mesmo que com a utilização de intervalos de isquemia e reperfusão diferentes ou de animais doentes ou sadios na metodologia, utilizando-se uma avaliação enzimática precoce ou tardia 8,9,11,13,20 , chegaram às mesmas conclusões: há benefício da utilização do clampeamento intermitente, especialmente em situações de necessidade de isquemia prolongada.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Techniques of occluding hepatic inflow (Pringle maneuver) and outflow are being investigated as means of reducing blood loss in healthy livers [16]. However, the ability of cirrhotic liver to tolerate blood flow occlusion has not yet been fully elucidated and may limit its use in this situation [35]. In a pilot study involving 15 patients with cirrhosis who had hepatic inflow occlusion (Pringle maneuver) for 9-32 minutes during hepatic resection, a significant decrease in blood loss was achieved compared to a similar group of 15 patients operated on without the use of blood flow occlusion.…”
Section: Possible Interventionsmentioning
confidence: 99%